Design and control of an overactuated UAV for application in urban airspace - Singh, Karanjot (Nanyang Technological University, 2023)
The future of low altitude urban airspace utilization is poised to be transformed by the increasing dominance of small Unmanned Aerial Vehicles (UAVs). Their application can essentially be categorized as a threefold problem: establishing the regulatory principles for UAV operation, identification of the infrastructure needed to monitor the UAVs and ensure they adhere to the rules, and laying out the minimum performance requirements of the platforms so that they are capable of meeting the flight standards. This work addresses the pressing challenge of enhancing the performance envelope of small UAVs. The primary aim of this research is to develop an innovative overactuated multirotor system that augments UAV maneuverability, fault tolerance and operational safety. A crucial aspect of this study is overcoming the inherent underactuation limitations in standard quadrotors. This challenge is addressed through active propeller tilting, investigated in-depth through extensive real-world flight tests and simulations. The developed quadrotor, aptly named QuadPlus, efficiently combines actuator redundancy and thrust vectoring via propeller rotation in a compact package, compared to its state-of-the-art counterparts. Furthermore, a cascade control methodology based on incremental control allocation is devised to ensure stable attitude and velocity tracking even in the presence of actuator saturation and external disturbances during flight operations. The study showcases the successful realization of the QuadPlus multirotor system with an impressive 12 degrees of freedom. The innovative design allows for independent bi-axial tilting of 115 ° and 180 ° about two perpendicular axes while keeping the mechanical complexity relatively low. Real-world flight tests demonstrate the efficacy of the control methodology, showcasing stable hover and trajectory tracking in a desired hyperplane with accurate attitude tracking. Different test cases demonstrating the capability of QuadPlus to achieve symmetric (20 ° roll and pitch) and asymmetric (20 ° roll, 10 ° pitch and vice versa) attitude with static hover are presented. It is also tested against Level 3 wind conditions of 4m/s and actuator saturation. The extensive bi-axial tilting capability of the system enables precise force production of up to 9N for contact-based tasks, presenting promising potential for inspection-related applications. The research also significantly contributes to ensuring fail-safe UAV operations. A centralized fault-tolerant control (FTC) framework based on nonlinear model predictive control (NMPC) is proposed to address potential propeller failures, effectively mitigating attitude deviations and enhancing overall system control. The FTC framework is validated through intensive simulations, proving its effectiveness in maintaining stable flight even in the presence of failures. The system is successfully tested against a single propeller failure while following an attitude of 30 ° each in roll and pitch. It is also successfully tested for failure recovery in aggressive flights following an 8-shaped trajectory with the attitude varying between ±30 ° for roll and pitch, and ±25 ° for yaw. The corresponding maximum deviations from the commanded trajectory are observed to be within acceptable limits. Additionally, the research introduces a novel approach for on-board state-of-health (SoH) diagnostics of the battery, a critical component of the multirotor system. The energy equilibrium approach enables better management of battery performance, ensuring safe and reliable UAV operations while avoiding rapid performance deterioration. Experimental work is performed to validate the model. However, further analysis onboard QuadPlus is presented as future work as part of realizing the fault tolerance capabilities. It is hypothesized that the integration of the SoH diagnostics into the flight controller will help keep the current drawn within the safe functional limits of the battery. In summary, this research substantially advances the field of UAV technology by presenting a groundbreaking solution to the challenges posed by low altitude urban airspace utilization. The innovative overactuated multirotor system, QuadPlus, coupled with the fault-tolerant control framework and on-board component diagnostics approach, holds immense potential for inspection-related applications and interactions with the physical environment.